Sacred Spaces in the Digital Age : Perceptions of Lutheran Christian Priests on Augmented Reality at Holy Sites - Laato, Samuli; Rauti, Sampsa; Laato, Anni Maria; Al-Msallam, Samaan; Jung, Sangwon; Sutinen, Erkki; Hamari, Juho (United States, 2025)
The concepts of sacred places and spaces appear throughout religions globally. Places such as churches, cathedrals, temples, mosques, synagogues and graveyards are given special meanings, both functionally and spiritually, and separated from the ordinary. Recently location-based augmented reality (AR) technologies and applications have become widespread, and this raises questions regarding how AR content relates to sacred places. In this study, we approached this complex topic by asking clergy of the Lutheran Christian Church (N=47) to reflect on associated phenomena. We approached the data via reflexive thematic analysis and uncovered tensions related to (1) connected vs detached from sacredness; (2) supporting the spiritual purpose of the space vs conflicting with it; and (3) maintaining tradition vs embracing innovation. Overall, our findings suggest that AR technologies and products impact sacred spaces on multiple levels, but currently there is no consensus among the clergy on the impact of these changes.
IMX '24: Proceedings of the 2024 ACM International Conference on Interactive Media Experiences